Creating virtual communities of practice for learning technology in higher education: a response by the author - Jacqueline A. Dempster (Association for Learning Technology, 2004)
Cathy Gunn's response to the paper was highly gratifying and raises a set of interesting points that I welcome the opportunity to explore more deeply. There were many considerations too complex to address in the paper and we accept the danger of oversimplification. Our summary of the RESULTs Network development was effectively a first attempt to match human values and behaviours to technical systems. Gunn suggests that a key element missing from our scenario is in having ‘a compelling reason for users to access the resources and participate in the communities provided'. The factors at play in terms of ‘motivation to participate' were extensively researched in the user participation study. A full reading is available in Beetham (2001). Nevertheless, there remains an important question about the process of adoption and participation. I would like therefore to take up the challenge of considering further the idea that communities of practice must ‘evolve' and cannot be ‘created'.